Assessment of Protective Effects of Carvacrol on Haloperidol-Induced Oxidative Stress and Genotoxicity in Human Peripheral Blood Lymphocytes - Ehsan Zamani; Alireza Ahmadi Shad; Hediye Fatemi; Saba Mahboubi; Azadeh Motavallian; Mehdi Evazalipour (Journal of Toxicology)
Haloperidol is a first-generation antipsychotic drug that has several indications in a wide range of mental conditions. The extensive prescription of haloperidol is correlated with some less-known adverse effects such as genotoxicity. Carvacrol is a monoterpenoid mainly found in oregano and thyme. It has the potential to scavenge free radicals in addition to increasing antioxidant defense enzyme activities and glutathione levels. In this study, we attempted to explore the possible potential of haloperidol in inducing genotoxicity in human peripheral lymphocytes as well as the protective role of carvacrol against this effect. The lymphocytes were divided into separate groups as follows: control group (cosolvent and NS); carvacrol group (5 μM); haloperidol group (25, 50, and 100 ng/ml); haloperidol (25, 50, and 100 ng/ml) + carvacrol (5 μM); positive control (0.8 μg/ml Cisplatin). After 24 hours of treatment, we conducted a cytokinesis-Block micronucleus test and an alkaline comet assay in order to determine genetic damage. Additionally, we measured glutathione and MDA levels as the biomarkers associated with oxidative stress. Significant increases in the levels of genotoxicity biomarkers (micronucleus frequency, DNA percentage in tail and tail moment) were observed in haloperidol-treated cells. The result of our oxidative stress tests also demonstrated that haloperidol had the potential to induce oxidative stress via reducing the levels of glutathione and increasing lipid peroxidation. Treatment with carvacrol significantly decreased the genotoxic events. It can be presumed that the induction of oxidative stress by haloperidol is the critical event associated with haloperidol-mediated genotoxicity. Therefore, using carvacrol as a natural antioxidant protected human lymphocytes against haloperidol genetic damage.